2019
DOI: 10.1590/1517-869220192505189240
|View full text |Cite
|
Sign up to set email alerts
|

Postural Adjustments of Active Youths in Perturbation and Dual-Task Conditions

Abstract: Introduction Cognitive components are necessary to maintain posture during external perturbations. However, few studies have investigated postural control when external perturbations are associated with a concomitant cognitive task (DT). Objectives To analyze the behavior of reactive adjustments after perturbation with different intensities and displacements in active young adults; and to analyze the influence of DT on predictive and reactive adjustments in different perturbation conditions. Methods Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Reduced balance performance during dual tasks is mostly observed in older populations (e.g., larger sway areas) but has also been observed in young adults (Riley et al, 2003;Swan et al, 2004), however with mixed results. For example, Beretta et al (2019) observed that young adults reduced their CoP sway during dual tasking on a moving platform. Their cognitive task was to report how many times a preset number appeared in the audio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced balance performance during dual tasks is mostly observed in older populations (e.g., larger sway areas) but has also been observed in young adults (Riley et al, 2003;Swan et al, 2004), however with mixed results. For example, Beretta et al (2019) observed that young adults reduced their CoP sway during dual tasking on a moving platform. Their cognitive task was to report how many times a preset number appeared in the audio.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Beretta et al. (2019) observed that young adults reduced their CoP sway during dual tasking on a moving platform. Their cognitive task was to report how many times a preset number appeared in the audio.…”
Section: Introductionmentioning
confidence: 99%